Training for Enhancing Farmers Capacity Using Cultivation Technology and High-Quality Seeds by CAP Panah Merah in Kabangka District - Wiwiek Rindayati; Dominicus Savio Priyarsono; Musram Abadi; La Ode Nafiu; Gerhana; Bambang Wihardi (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
The agricultural sector is the foundation of the national economy, where the basic needs of the Indonesian people can be fulfilled through agricultural products. Vegetables, as one of the main food sources, require proper cultivation processes to produce high-quality products in sufficient quantities. Several studies have shown that training and extension methods are effective in improving farmers capacities. This training activity aims to enhance farmers capacity through cultivation technology and the use of high-quality CAP Panah Merah seeds. The program was carried out in July 2024 with the final evaluation in November 2024, located in Wasungi Village Kabangka District Muna Regency Southeast Sulawesi. The training participants included farmer groups from Kabangka District, with the presence of the Muna Agriculture Department, Kabangka Agricultural Extension Agency and the District Government. The results show that this training is an effective strategy to help farmers improve agricultural production. Positive impacts were observed in the final evaluation, with satisfying production outcomes and improved farmers welfare. The support of advanced technology and the use of high-quality seeds, such as CAP Panah Merah, has proven to increase productivity and farmers income while supporting the sustainability of their agricultural businesses. This program not only benefits farmers but also enhances the effectiveness of program implementation by stakeholders.